Analisis Hukum Islam Terhadap Putusan Pengadilan Agama Jember tentang Penetapan Status Ahli Waris Non Muslim (No.1050/Pdt.G/2016/Pa.Jr) - Saddam Husein; Martoyo Martoyo (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
The Religious Court is a court that has the authority to adjudicate cases for Muslims. In the Jember Religious Court's decision No.1050 / Pdt.G / 2016 / PA.Jr explained that the Plaintiff, who is one of the children of the heir and the other five plaintiffs, filed a lawsuit against four defendants and seven co-defendants regarding inheritance cases; in this case, the inheritance is still not distributed by the heir to the heirs entirely. And the property is still controlled by one defendant. Also, the decision of the panel of judges is interesting. From the inheritance distributed in Islam, there are descendants of heirs who are non-Muslim who also receive a share of the estate. The research method used in this study is a normative research method with two approaches. Those are the case and the statute approach. This study found that: First, the construction of the case on the Jember Religious Court No. 1050 / Pdt.G / 2016 / PA.Jr is the five Plaintiffs against the eleven defendants. The plaintiffs filed the lawsuit because they stated that their parents were Muslims. With this, the plaintiffs want their inheritance to be distributed under Islamic law. Second, the Decidendi Ratio of the Panel of Judges in deciding cases is the provision of Article 49 paragraph (1) letter (b) of Law no. 7 of 1989 the Religious Court's authority to handle Inheritance cases for people who are Muslim.